Role of School Administration Towards Caring Gifted Students in Model Secondary Schools in Aden Governorate from the Teachers’ Point of View - Abdullah, Fahad Ali; Saleh, Dhahiba Saeed (Journal of Educational and Psychological Sciences, 2025)
This research aims at identifying the role of school administration towards caring gifted student in model secondary schools in Aden Governorate from the teachers’ point of view. A questionnaire was used based on the 2010 National Association for Gifted Children (NAGC) program standard. The questionnaire consisted of six sections which are: education and development, assessment, curriculum and teaching planning, learning environments, program management, and professional development. The research community amounts to 124 male and females and d a comprehensive inventory method was used due to the small size of the study population. The collected data were statistically analyzed using the Statistical Packages for Social Sciences (SPSS). The research concluded with a number of findings, the most important of which are: the role of school administration towards caring talented students in model secondary schools in Aden governorate was positive average degree overall in all the sections of the questionnaire, there were statistically significant differences between the sample members’ estimates of the role of school administration in caring for the gifted in model secondary schools in Aden Governorate attributed to the gender variable in the sections (education and development, learning environments, and professional development) in favor of females while in the section (program management) in favor of males and here were statistically significant differences between the sample members’ estimates of the role of school administration in caring for the gifted in model secondary schools in Aden Governorate, attributed to the educational qualification variable in favor of higher than a bachelor’s degree.